PENGARUH PROFITABILITAS DAN PERKEMBANGAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN SUSTAINABILITY REPORT SEBAGAI VARIABLE MODERATING - Yulianto Imantaka; Imam Wahyudi (Jurnal Kelola: Jurnal Ilmu Sosial, 2022)
The purpose of this study is to investigate the impact of profitability and corporate growth on corporate value, using the sustainability report of SRI-KEHATI index companies listed on the Indonesia Stock Exchange as a moderation variable, partially or simultaneously. is. The purpose of this study is to compare the results of previous studies. The sample was selected using the sampling method of interest. The samples used in this survey were 8 companies, and the observation period was 4 years (2016-2019).. Data processing using E-views 9. This study used descriptive statistical analysis and panel data regression to test hypotheses.